2014
DOI: 10.3906/vet-1212-36
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in mussels (Mytilus galloprovincialis) harvested from North Aegean coastal area

Abstract: One hundred and two samples of mussels (Mytilus galloprovincialis), harvested from approved shellfish coastal water in northern Greece, were screened for the presence and antimicrobial resistance of Listeria monocytogenes. Listeria spp. were isolated according to International Organization for Standardization method 11290-1: 1996/FDAM 1: 2004(E) and identified using a multiplex polymerase chain reaction (PCR) system. The serovar identity of L. monocytogenes isolates was also determined with a multiplex PCR ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The species Listeria monocytogenes is a food-borne pathogen detected in mussels and in various types of seafood, including shrimps, lobsters, crabs and fish (Elliot and Kvenberg, 2000;Rodas-Su arez et al, 2006). Soultos et al (2014) demonstrated that L. monocytogenes is not commonly found in mussels harvested in the North Aegean Sea. However, there the potential for mussels to be contaminated by other Listeria species is high.…”
Section: Bacteria and Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…The species Listeria monocytogenes is a food-borne pathogen detected in mussels and in various types of seafood, including shrimps, lobsters, crabs and fish (Elliot and Kvenberg, 2000;Rodas-Su arez et al, 2006). Soultos et al (2014) demonstrated that L. monocytogenes is not commonly found in mussels harvested in the North Aegean Sea. However, there the potential for mussels to be contaminated by other Listeria species is high.…”
Section: Bacteria and Microalgaementioning
confidence: 99%
“…Soultos et al . (2014) demonstrated that L . monocytogenes is not commonly found in mussels harvested in the North Aegean Sea.…”
Section: Pathogensmentioning
confidence: 99%
“…Listeria spp., especially L. monocytogenes, were reported in farmed mussels in the North Aegean Sea ( [61]. Of relevance, [62] noted that contamination with listeria could occur as a result of improper harvesting, handling, processing and sanitation [63].…”
Section: Bacterial Isolates From Seafood In Scotlandmentioning
confidence: 99%